Improving risk indexes for Alzheimer's disease and related dementias for use in midlife. Issue 5 (6th October 2022) - Reuben, Aaron; Moffitt, Terrie E; Abraham, Wickliffe C; Ambler, Antony; Elliott, Maxwell L; Hariri, Ahmad R; Harrington, Honalee; Hogan, Sean; Houts, Renate M; Ireland, David; Knodt, Annchen R; Leung, Joan; et al.
Abstract: Knowledge of a person's risk for Alzheimer's disease and related dementias (ADRDs) is required to triage candidates for preventive interventions, surveillance, and treatment trials. ADRD risk indexes exist for this purpose, but each includes only a subset of known risk factors. Information missing from published indexes could improve risk prediction. In the Dunedin Study of a population-representative New Zealand-based birth cohort followed to midlife ( N = 938, 49.5% female), we compared associations of four leading risk indexes with midlife antecedents of ADRD against a novel benchmark index comprised of nearly all known ADRD risk factors, the Dunedin ADRD Risk Benchmark (DunedinARB). Existing indexes included the Cardiovascular Risk Factors, Aging, and Dementia index (CAIDE), LIfestyle for BRAin health index (LIBRA), Australian National University Alzheimer's Disease Risk Index (ANU-ADRI), and risks selected by the Lancet Commission on Dementia. The Dunedin benchmark was comprised of 48 separate indicators of risk organized into 10 conceptually distinct risk domains. Midlife antecedents of ADRD treated as outcome measures included age-45 measures of brain structural integrity [magnetic resonance imaging-assessed: (i) machine-learning-algorithm-estimated brain age, (ii) log-transformed volume of white matter hyperintensities, and (iii) mean grey matter volume of the hippocampus] and measures of brain functional integrity [(i) objective cognitive function assessed via the Wechsler Adult Intelligence Scale-IV, (ii) subjective problems in everyday cognitive function, and (iii) objective cognitive decline measured as residualized change in cognitive scores from childhood to midlife on matched Weschler Intelligence scales]. All indexes were quantitatively distributed and proved informative about midlife antecedents of ADRD, including algorithm-estimated brain age ( β 's from 0.16 to 0.22), white matter hyperintensities volume ( β 's from 0.16 to 0.19), hippocampal volume ( β 's from −0.08 to −0.11), tested cognitive deficits ( β 's from −0.36 to −0.49), everyday cognitive problems ( β 's from 0.14 to 0.38), and longitudinal cognitive decline ( β 's from −0.18 to −0.26). Existing indexes compared favourably to the comprehensive benchmark in their association with the brain structural integrity measures but were outperformed in their association with the functional integrity measures, particularly subjective cognitive problems and tested cognitive decline. Results indicated that existing indexes could be improved with targeted additions, particularly of measures assessing socioeconomic status, physical and sensory function, epigenetic aging, and subjective overall health. Existing premorbid ADRD risk indexes perform well in identifying linear gradients of risk among members of the general population at midlife, even when they include only a small subset of potential risk factors. They could be improved, however, with targeted additions to more holistically capture the different facets of risk for this multiply determined, age-related disease. Abstract : Reuben et al . report that existing dementia-risk indexes are informative about brain health in the general population decades before dementia symptoms emerge, even when the indexes include only a subset of potential risks. Comparisons to a novel comprehensive risk-benchmark indicated that targeted risk-factor additions could improve the selection of at-risk individuals. Graphical Abstract: Graphical abstract